Neutrophils and aortic medial amyloid: mutually beneficial or a dangerous combination? - Maerivoet, Alana; Shirley, Sarah; Price, Rebecca; Wilkinson, David; Wright, Helen L.; Madine, Jillian (Frontiers in Immunology, 2026)
IntroductionAmyloid deposition and inflammation are associated with many human diseases, with inflammatory cells found co-localised with amyloid in a range of tissues. Medin is the peptide that forms the most common localised amyloid in the aortic medial layer, yet remarkably little is known about its role in disease or factors that modulate its aggregation.MethodsWe investigated the effect of neutrophil degranulation supernatants on medin fibril formation in vitro and explored the impact of inhibiting proteolytic components of neutrophil degranulation on aggregation using Thioflavin T fluorescence, transmission electron microscopy and cell viability analyses. ResultsWe showed that neutrophil supernatants reduced fibril formation of medin and its associated cell toxicity. Addition of inhibitors targeting MMPs (GM6001) and serine proteases (AEBSF) reversed the effects of neutrophils on fibril formation and cell toxicity. In contrast, inhibiting cysteine proteases using E64 showed comparable low ThT fluorescence and a lack of fibrils similar to what is observed for medin in the presence of neutrophil supernatants alone. However, despite appearing comparable to neutrophils alone, species produced showed significantly increased cell toxicity of up to 60% (P<0.0001). DiscussionThis data has implications for understanding the role of neutrophil-mediated inflammation in medin-associated pathologies and provides avenues to explore for future therapeutic intervention.